3-D transient heat transfer in a simulated solar-heated adsorption panel - De Leon, Rizalinda L. (2006)
Adsorption panels are used for refrigeration and heat pump applications. These are operated in a cycle of desorption and adsorption. Desorption may be done by heating the adsorption panel using solar heat. Cycle performance is significantly affected by the thermal characteristics of the system and design of panel.